Just so stories - Kipling, Rudyard (Oxford University Press; London, 2006)
Just So Stories by Rudyard Kipling is a collection of whimsical origin tales that explain how various animals and natural phenomena came to be, often with playful and imaginative explanations. These stories, filled with moral lessons and humor, are written for children but captivate readers of all ages with their charm and creativity.